A longitudinal study shows intermittent colonization by Staphylococcus aureus with a high genetic diversity in hemodialysis patients (2021)
ABSTRACT : Staphylococcus aureus colonization increases the risk of invasive infections in different groups of patients. We analyzed the dynamics and factors associated with S. aureus colonization in hemodialysis patients. A longitudinal study was conducted at a dialysis center associated with a tertiary health care institution. S. aureus colonization was assessed three times in nostrils and on the skin and was classified as absent, intermittent or persistent. The molecular analysis included pulsed-field gel electrophoresis (PFGE) and spa-typing. Clonal complex was inferred from spa-typing. A model of generalized estimating equations was performed to determine the factors associated with colonization. A total of 210 patients were included. Colonization by methicillin-susceptible (MSSA) and methicillin-resistant (MRSA) isolates was 29.1 % vs. 4.8 %, 29.2 % vs. 6.7 % and 24.1 % vs. 7.1 % in the first, second and third screenings respectively. Most of the colonized patients were intermittent carriers (77.8 %, n = 63). PFGE and spa-typing revealed a high genetic diversity. One third (33.3 %) of the carriers classified as persistent had different clones during follow-up. Clonal complex 8 was frequent among MSSA (28 %) and MRSA (59 %) isolates. Current smoking (OR:7.22, 95 %CI 2.24–23.27), Charlson index (OR:1.22, 95 %CI 1.03–1.43) and previous infection by S. aureus (OR:2.41; 95 %CI:1.09− 5.30) were associated with colonization by this microorganism. Colonization increased the risk of bacteremia (HR = 4.9; 95 % CI: 1.9–12.9). In conclusion, the colonization by S. aureus in hemodialysis patients changes over time and acquisition of new clones is a frequent event. These results evidence that patients are repeatedly recolonizing from hospitals, dialysis units and their homes. On the other hand, factors not associated with healthcare, as smoking, can increase the risk of colonization.